A real-time tripodal colorimetric/fluorescence sensor for multiple target metal ions. (August 2018) - Diana, Rosita; Caruso, Ugo; Concilio, Simona; Piotto, Stefano; Tuzi, Angela; Panunzi, Barbara
Abstract: In this work we report on the synthesis of a pyridyl/phenolic/benzothiazole functionalized colorimetric receptor (BPAP ) that can selectively recognise Fe(III) and Fe(II) ions in aqueous medium with visible, naked eye colour changes. Moreover, BPAP behaves as a 'turn-on' fluorescent chemosensor, showing an excellent sensitivity towards Zn 2+ and Cd 2+ cations in water by exhibiting fluorometric change.BPAP exhibited a visible detection limit of 5.5 μM and 2.5 μM for Fe 3+ and Fe 2+, respectively, and a fluorometric selectivity towards Zn 2+ and Cd 2+ ions with lower detection limits of 205 nM and 642 nM. To understand the mode of binding to the sensor, both the nude sensor and the Zn-complex were isolated and characterized by X-ray crystallography. InZn-BPAP, the ligand acts as neutral tridentate through Npyridine, Namine and Namide donor atoms. The N atom of benzothiazole group and the OH group of the phenole unit are not coordinated. Computational DFT study was performed on the free ligandBPAP and complex with Zn 2+ to investigate the interaction site, to calculate the energies of the frontier molecular orbitals and to corroborate some of the experimental results. Graphical abstract: Highlights: A novel tripodal pyridyl/phenolic/benzothiazole colorimetric receptor (BPAP ) and its zinc complex were prepared. BPAP can selectively recognise Fe(III) and Fe(II) ions in aqueous medium with visible, naked eye colour changes. BPAP acts as a fluorescence sensor in presence of Cd(II) and Zn(II).